Bendamustine and its role in the treatment of unfit patients with chronic lymphocytic leukaemia: a perspective review. (June 2017) - Al-Sawaf, Othman; Cramer, Paula; Goede, Valentin; Hallek, Michael; Pflug, Natali
With a median age of 72 years at first diagnosis, chronic lymphocytic leukaemia (CLL) is a disease of the elderly. At this age, many patients cannot bear an intensive chemoimmunotherapy like fludarabine, cyclophosphamide and rituximab (FCR), and therapeutic decisions are commonly complicated by a high burden of accompanying comorbidities. Clinical trials, on the other hand, are mostly designed to include a far healthier and younger trial population, with a median age in most studies well below 70 years, leading to an insufficient reflection of clinical reality. With the introduction of new targeted therapies, treatment of CLL is currently undergoing a profound change. New compounds like ibrutinib or idelalisib have enlarged the therapeutic options in treating CLL. However, so far, these oral medications imply continuous intake by the patient, which will at some point lead to the issue of adherence in most patients. In addition, long-term experiences are largely missing. In this setting, one of the oldest chemoactive substances remains a viable option for many CLL patients and their treating physicians: bendamustine, a nitrogen–mustard derivative, has proven to be a safe and efficient agent for treatment of CLL in the first- and second-line setting. In particular, there is some evidence that the substance is relatively well tolerated in elderly and unfit patients. In this review, we summarize the current data on bendamustine in the treatment of elderly and unfit patients with CLL and aim to provide a concise analysis and outlook on the current and future role of this substance in the era of new targeted agents.